PERANCANGAN VISUAL IDENTITY BARAKA KAFE PADA MEDIA ADPRINT - FAKHRUL RIJAL YE, Hendra Afriwan, S.Sn., M.Sn., San Ahdi, M.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Baraka Kafe is a cafe that served drink in the form of whole milk and coffee. It also serves a variety of snacks like cake and bread. Baraka Kafe war formerly known as Susu Murni Kafe. Therefore, now it designed with visual identity and logo with color that has a typography to representing the concept of Baraka Kafe, and make it easyly to remembered by consumers. The logo will be placed in several media, so it would be a media for direct and indirect promotion as well.The analytical methods used in the design of visual identity Baraka Kafe is using the SWOT (Strength, Weakness, Opportunity, Threat) analytical in used as a visual identity plan and design to highlight the characteristic to Baraka Kafe. The design of this visual identity includes the media: manual book, paper bas, cups and cup papper, poster, x-banner, handbook, aprons, T-shirts, pins and stickers. Hopefully, by the visual identity design can help increase brand royalties and gain brand awareness for the results of the design precisely targeted, effective and communicative so it may be better known by the public.Key Word: Visual Identity, Logo, Baraka.